An updated practical guideline on use of molnupiravir and comparison with agents having emergency use authorization for treatment of COVID-19. Issue 2 (February 2022) - Singh, Awadhesh Kumar; Singh, Akriti; Singh, Ritu; Misra, Anoop
Abstract: Background and aims: Molnupiravir is a newer oral antiviral drug that has recently received emergency use authorization (EUA) in USA, UK and India. We aim to conduct an update on our previous systematic review to provide practical clinical guideline for using molnupiravir in patients with COVID-19. Methods: We systematically searched the electronic database of PubMed, MedRxiv and Google Scholar until January 5, 2022, using key MeSH keywords. Results: Final result of phase 3 study in 1433 non-hospitalized COVID-19 patients showed a significant reduction in composite risk of hospital admission or death (absolute risk difference, −3.0% [95% confidence interval CI, −5.9 to −0.1%]; 1-sided P = 0.02) although with a non-significant 31% relative risk reduction (RRR). RRR for death alone was 89% (95% CI, 14 to 99; P-value not reported). Number needed to treat to prevent 1 death or 1 hospitalization or death composite appears to be closely competitive to other agents having EUA in people with COVID-19. However, cost-wise molnupiravir is comparatively cheaper compared to all other agents. Conclusion: Molnupiravir could be a useful agent in non-pregnant unvaccinated adults with COVID-19 who are at increased risk of severity including hospitalization. However, it is effective only when used within 5-days of onset of symptoms. A 5-days course seems to be safe without any obvious short-term side effects. Highlights: Molnupiravir has been studied in mild-to-moderate COVID-19 at risk for increased severity and found to reduce primary outcomes in unvaccinated people. Role of molnupiravir in post-vaccinated breakthrough infection is not known and it was not effective in people with past history of COVID-19. Despite some concern in preclinical studies, 5-days course of molnupiravir in adults and non-pregnant COVID-19 patients appeared to be safe. Effectiveness of molnupiravir is competitive to three monoclonal antibodies, remdesivir and nirmatrelvir-ritonavir, with a relatively lower cost.